2013
DOI: 10.1186/1532-429x-15-94
|View full text |Cite
|
Sign up to set email alerts
|

At-risk but viable myocardium in a large animal model of non ST-segment elevation acute coronary syndrome: cardiovascular magnetic resonance with ex vivo validation

Abstract: BackgroundPatients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) have varying degrees of salvageable myocardium at risk of irreversible injury. We hypothesized that a novel model of NSTE-ACS produces acute myocardial injury, measured by increased T2 cardiovascular magnetic resonance (CMR), without significant necrosis by late gadolinium enhancement (LGE).MethodsIn a canine model, partial coronary stenosis was created and electrodes placed on the epicardium. Myocardial T2, an indicator of at-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…So far, different methods are currently used to induce transmural (STEMI) infarction in large animals, including the permanent ligation of the left anterior descending coronary artery (LAD) (14,15). Only recently, the reproduction of non-ST elevation (NSTE)-acute coronary syndrome (ACS) has been developed in a canine model (16). However, the observed damage was not irreversible cardiac damage (16), which means that no infarct (i.e., NSTEMI) was produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, different methods are currently used to induce transmural (STEMI) infarction in large animals, including the permanent ligation of the left anterior descending coronary artery (LAD) (14,15). Only recently, the reproduction of non-ST elevation (NSTE)-acute coronary syndrome (ACS) has been developed in a canine model (16). However, the observed damage was not irreversible cardiac damage (16), which means that no infarct (i.e., NSTEMI) was produced.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, the reproduction of non-ST elevation (NSTE)-acute coronary syndrome (ACS) has been developed in a canine model (16). However, the observed damage was not irreversible cardiac damage (16), which means that no infarct (i.e., NSTEMI) was produced. With this in mind, we developed an NSTEMI model that enabled the investigation of the efficacy of customized ELRs-hydrogel in the modulation of post-ischemic remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…We subsequently showed that myocardial edema by T2 CMR delineates at‐risk but salvageable myocardium in a large‐animal model of NSTE‐ACS 10. Thus, T2 CMR before angiography can delineate at‐risk but salvageable myocardium in NSTE‐ACS 11.…”
Section: Introductionmentioning
confidence: 90%
“…CMR is invaluable to the study of patients with ischaemic heart disease and has made a major impact on this field and is now widely used to delineate myocardial infarction, [ 161 , 162 ] and scarring, [ 163 ] although more recently non-contrast techniques to detect infarction have been described. The use of techniques to define myocardial edema, [ 164 166 ] myocardium at risk, [ 167 ] myocardial hemorrhage, and microvascular obstruction, [ 168 ] has also grown greatly. Work has moved on to evaluating the relation between myocardial damage and aspects of myocardial function such as dyssynchrony, remodelling, healing, and determining outcomes, [ 169 ] and the indication for novel treatments [ 170 172 ].…”
Section: Coronary Artery Diseasementioning
confidence: 99%